DETERMINANT PRODUCTIVITY OF HONORARY EMPLOYEES IN WATER IRIGATION AREA OBSERVATION OFFICES SELUMA - Budi Setiawan; Ahmad Soleh; Kaulan Kaulan (BIMA Journal (Business, Management, & Accounting Journal), 2020)
This study aims to analyze the determinants of the work productivity of honorary employees at the Seluma Irrigation Water Observers Regional Office. The method of collecting data is by distributing questionnaires to 42 honorary employees. Analysis of the data used is quantitative analysis, with the method of multiple linear regression, determination test, t test and F test. The results of SPSS analysis for windows version 16.0, obtained the regression equation Y = 2.239 + 0.231X1 + 0.653X2 + 0.378X3. The regression equation shows that there is a positive influence between morale, work discipline and organizational commitment to the work productivity of honorary employees at the Seluma Irrigation Water Observers Regional Office, and work discipline variables have the strongest influence on work productivity because it has the greatest regression coefficient value, namely .653. From the results of the determination test it is known that 85.3% of the work productivity of honorary employees at the Seluma Irrigation Water Irrigation Area Observers Office is influenced by morale, work discipline and organizational commitment. The t-test results showed that morale, work discipline and organizational commitment partially had a significant effect on the work productivity of honorary employees, because of the probability value of sig. 0.05. While the F (Anova) test results showed that work morale, work discipline and organizational commitment simultaneously had a significant influence on the work productivity of honorary employees at the Seluma Irrigation Water Irrigation Area Observers Office, where Fcount Ftable (80,169 2,850).